2023
DOI: 10.1161/cir.0000000000001112
|View full text |Cite
|
Sign up to set email alerts
|

Management of Acute Coronary Syndrome in the Older Adult Population: A Scientific Statement From the American Heart Association

Abstract: Diagnostic and therapeutic advances during the past decades have substantially improved health outcomes for patients with acute coronary syndrome. Both age-related physiological changes and accumulated cardiovascular risk factors increase the susceptibility to acute coronary syndrome over a lifetime. Compared with younger patients, outcomes for acute coronary syndrome in the large and growing demographic of older adults are relatively worse. Increased atherosclerotic plaque burden and complexity of anatomic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
82
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 190 publications
(298 reference statements)
1
82
0
Order By: Relevance
“…The standard of care for detecting myocardial injury is high-sensitivity cardiac troponin I (hs-cTn). However, certain conditions, such as myocardial fibrosis or chronic kidney disease, can result in higher baseline values and a lower positive predictive value (1). Compared with the first scientific statement on Acute Coronary Care in the Elderly published in 2007, (5,6) the latest document reported that more randomized controlled trials (RCTs) have involved older adults (1).…”
Section: Management Of Acs In Elderlymentioning
confidence: 99%
See 1 more Smart Citation
“…The standard of care for detecting myocardial injury is high-sensitivity cardiac troponin I (hs-cTn). However, certain conditions, such as myocardial fibrosis or chronic kidney disease, can result in higher baseline values and a lower positive predictive value (1). Compared with the first scientific statement on Acute Coronary Care in the Elderly published in 2007, (5,6) the latest document reported that more randomized controlled trials (RCTs) have involved older adults (1).…”
Section: Management Of Acs In Elderlymentioning
confidence: 99%
“…However, certain conditions, such as myocardial fibrosis or chronic kidney disease, can result in higher baseline values and a lower positive predictive value (1). Compared with the first scientific statement on Acute Coronary Care in the Elderly published in 2007, (5,6) the latest document reported that more randomized controlled trials (RCTs) have involved older adults (1). Both the After Eighty (2016) (7) suggests considering a medication review and deprescribing, lifestyle modifications and cardiac rehabilitation, comorbidity management, psychosocial support, socioeconomic factors, and education of both patients and caregivers.…”
Section: Management Of Acs In Elderlymentioning
confidence: 99%
“…Patients with ≥ 75 years of age represent a large and significant proportion of those admitted for acute coronary syndromes (ACS) in our hospitals [1]. Older patients frequently present with peculiar features and comorbidities (complex coronary lesions, anaemia, chronic kidney dysfunction, peripheral vascular disease) associated with geriatric syndromes (frailty, disability, cognitive impairment) that are relevant determinants of patients health and outcomes [2]. Older adults have frequently low-grade inflammation ("inflammaging") which has been associated with the occurrence of frailty and with the development of the atherosclerotic process [2].…”
mentioning
confidence: 99%
“…Older patients frequently present with peculiar features and comorbidities (complex coronary lesions, anaemia, chronic kidney dysfunction, peripheral vascular disease) associated with geriatric syndromes (frailty, disability, cognitive impairment) that are relevant determinants of patients health and outcomes [2]. Older adults have frequently low-grade inflammation ("inflammaging") which has been associated with the occurrence of frailty and with the development of the atherosclerotic process [2]. The prevalence of frailty increases as age advances and is more frequent among elderly women: it is present in more than 20% of patients with 80 to 84 years of age [2,3].…”
mentioning
confidence: 99%
See 1 more Smart Citation